PENGARUH CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL PEMBELAJARAN TEMATIK KELAS IV SDN 32 PONTIANAK - Gunesa, Kalista; Sabri, Tahmid; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to test the effect of the application of contextual teaching and learning to the thematic learning outcomes IV in class grade students at SDN 32 Shouteast Pontianak. The method used is the experimental method, a form of research Quasi Experimental Design, with the type of Non-Equivalent Control Group Design. The population in this research is all fourth grade students consisting of 82 students. The research sample consisted of class IV A as a control class of 24 and IV B as an experimental class of 30. The data collection tool is a written test in the form of multiple choice. Based on data analysis, the average post-test results of the experimental class were 74,2 while the average post-test results of the control class were 68,75. The results of the t-test are obtained tcount of 4,04, and ttable (α = 5% (dk = 30 + 24 - 2 = 52) of 1,67. Because tcount (4,04)> ttable (1,67), Ha is accepted. From the results of the calculation of the effect size obtained is 0,51(medium criteria). This means that the application of contextual teacing and learning have a good influence on the thematic learning outcomes IV in class grade students at SDN 32 Shouteast Pontianak. Keywords: Contextual Teaching and Leaning, Thematic, learning Outcomes